Exchange rates and stock prices: how do they interact in Eastern Europe? - Ozcelebi, Oguzhan; Yildirim, Nurtac (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
In this study, we estimate Structural Vector Error Correction (SVEC) models to analyze the effects of the exchange rate on stock prices and vice versa in the Czech Republic, Hungary, Poland and Turkey. Our empirical findings imply that for all cases, the fluctuations in exchange rates may have a considerable role in the variation in stock markets, while variations in stock prices may have macroeconomic consequences by leading to changes in real exchange rates. We also found that the relationship between real exchange rates and stock prices in these countries may be induced by the monetary policy decisions of the Fed and other domestic and foreign factors. Our results stress the importance of the derivation of the optimal economic policy framework to analyze the interaction between exchange rates and stock prices. In this respect, we suggest the use of Dynamic Stochastic General Equilibrium (DSGE) modelling with country-specific and global factors to determine the economic polices sustaining financial and economic stability for the Czech Republic, Hungary, Poland and Turkey
Argument Oeconomica, 2016, Nr 1 (36), s. 31-65
Keywords: exchange rates; stock prices; SVEC model; Eastern European countries